(untitled) (Economic and Political Thought, 2024)
This paper addresses issues connected with economic growth, how the theory on it has changed and also what its potential determinants are. In order to do so, the panel data was constructed for 129 countries with the time period of 1975-2015. In addition to this, the paper also accounts for the model uncertainty as well as reverse causality issues that may arise while dealing with such data. The methodology applied in the research consists of the Moral-Benito (2016) framework combined with the bayesian model averaging method (BMA). Out of the five variables, only one turned out to be fragile. The other four appeared to be robust with three of them at the most restrictive level. What is more, the paper also presents the potential reasoning behind obtained results and upholds the hypothesis that international trade has a positive impact on the economic growth.